Community-oriented practice: Examining corporate social responsibility and development activities in professional sport. Issue 3 (June 2019) - Rowe, Katie; Karg, Adam; Sherry, Emma
Highlights: Community activities of professional sport teams are examined drawing on CSR and SFD literature. We identify and categorises 1243 examples of community initiatives from leagues in the US, UK, and Australia. Fourteen types of activities and three broad groups (giving, activating, and capacity building) are identified. Differences between regions are observed in relation to the types of activities and focus of initiatives. Community-oriented practice is defined and positioned as the community-focused activities of professional sport teams. Abstract: Professional sport teams are increasingly engaging in activities that target community development agendas. Previous researchers have examined why teams engage in such activities and the value they derive from a corporate social responsibility (CSR) perspective; however, an understanding of the nature and focus of such activities is only beginning to emerge and further research attention is necessary. To address this gap, the authors draw on both CSR and sport-for-development (SFD) literature to examine community activities undertaken by professional sport teams. An exploratory case study methodology was employed, using a multi-case design to examine the activities of 70 professional sport teams across the commercially dominant league in each of three regions (Australia, the UK, and the US). A total of 1243 initiatives were recorded and analysed to build a profile of the nature and focus of the community activities undertaken. These were classified into 14 specific categories and analysis identified three core groups of activities: giving, activating and capacity building. Teams primarily targeted health and education agendas; however, differences were observed across regions. Teams in the US engaged more heavily in giving activities, whereas teams in the UK more commonly engaged in capacity-building activities. Variations were also observed with respect to target agenda, demonstrating differences within practices across regions. The authors propose community-oriented practices as a concept to describe the community-focused activities undertaken by professional sport teams at the intersection of CSR and SFD, and a working definition of this concept is offered.